2010
DOI: 10.1590/s1676-06032010000300032
|View full text |Cite
|
Sign up to set email alerts
|

Non-volant tetrapods from Reserva Biológica de Duas Bocas, State of Espírito Santo, Southeastern Brazil

Abstract: Reserva Biológica de Duas Bocas (2,910 ha) is one of the largest Atlantic forest remnants in the State of Espírito Santo, Southeastern Brazil. We recorded non-volant tetrapods in this area from May 2007 through April 2008, using pitfalls, live traps, camera traps, and diurnal and nocturnal opportunistic searches. In addition, we compiled available museum and literature records from this area. We documented 52 species of amphibians, 24 species of non-avian reptiles, and 39 species of non-volant mammals. Out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 12 publications
3
22
2
3
Order By: Relevance
“…The capture success (5.04%) obtained is higher to those found in other studies conducted in nearby areas such as Duas Bocas Biological Reserve (3.59%, see Tonini et al 2010) and Fonte Grande State Park (1.47%, in Santos et al 2004, to 1.90% in Caldara Jr and, in the state of Espírito Santo. Our sampling effort (832 trap-nights) was much lower than the others (3456 trap-nights at Fonte Grande and 7920 trap-nights at Duas Bocas), which may represent a bias in our list of species.…”
Section: Discussioncontrasting
confidence: 50%
“…The capture success (5.04%) obtained is higher to those found in other studies conducted in nearby areas such as Duas Bocas Biological Reserve (3.59%, see Tonini et al 2010) and Fonte Grande State Park (1.47%, in Santos et al 2004, to 1.90% in Caldara Jr and, in the state of Espírito Santo. Our sampling effort (832 trap-nights) was much lower than the others (3456 trap-nights at Fonte Grande and 7920 trap-nights at Duas Bocas), which may represent a bias in our list of species.…”
Section: Discussioncontrasting
confidence: 50%
“…The use of pitfall traps may render the collection of additional leaf-litter frogs (Terrarana and Cycloramphidae), which are of difficult collection and observation in visual surveys. As a good example, during recent fieldwork in Duas Bocas, Tonini et al (2010) found 52 species, 18 more species than an inventory published few years before (Prado and Pombal 2005). Several of the additional records found by Tonini et al (2010) were representatives of terrestrial secretive species, most likely only sampled because of the use of traps.…”
Section: Resultsmentioning
confidence: 97%
“…Published amphibian inventories for the Espírito Santo are scant and generally based on rapid inventories (but see Tonini et al 2010). In a recent work Almeida et al (2011) recorded 133 amphibian species occurring in the state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muitos dos principais estudos de levantamento realizados no Estado precedem à publicação da lista (Ramos & Gasparini, 2004;Prado & Pombal, 2005;Rödder et al, 2007;Teixeira et al, 2008;Ferreira et al, 2010;Tonini et al, 2010 Almeida et al (2011). Há de se reforçar, todavia, que mesmo estes estudos em áreas bastante estudadas são de extrema importância, pois geralmente resultam no registro de espécies não encontradas anteriormente, caso um esforço maior seja empregado.…”
Section: Diversidade De Anuros No Espírito Santounclassified